ANALISIS PERSEPSI MASYARAKAT LINGKUNGAN SWETA TIMUR TERHADAP PENGGUNAAN APLIKASI BRIMO SEBAGAI LAYANAN KEUANGAN DI ERA TRANSFORMASI DIGITAL - Dyah Paramitha, Ni Komang Dyah Paramitha; Asmara Yanti , Ni Nyoman Suli Asmara Yanti (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study aims to analyze the perceptions of the Sweta Timur community regarding the use of the BRImo application as a digital financial service in the era of digital transformation. The background of this research is based on the rapid development of information technology, which has driven the banking sector to innovate in providing digital-based financial services that are easily accessible, fast, secure, and efficient. BRImo, as one of Bank Rakyat Indonesia's (BRI) digital innovations, exists to meet the community's need for easy financial transactions within a single, integrated platform. This study employs a descriptive qualitative approach to in-depth explore the community's views, experiences, and perceptions regarding the use of the BRImo application. The study took place in the Sweta Timur community, Cakranegara District, Mataram City, considering the area's diverse socioeconomic conditions and relatively advanced level of digital service adoption. The study was scheduled for October to December 2025. Informants were selected using a purposive sampling technique, with participants selected based on specific criteria: residing in the Sweta Timur community, being at least 17 years old, and having experience using BRImo. Five informants with varying occupational and educational backgrounds were selected, including civil servants (PNS), private sector employees, traders, and students. This diversity is expected to provide a representative picture of perceptions regarding digital financial services within the community. Data collection was conducted using three techniques: in-depth interviews, observation, and documentation study. Interviews aimed to uncover user perceptions, motivations, and experiences; observation was used to directly observe application usage behavior; and documentation served to supplement the data through written sources such as application guides and supporting literature. Data validity was tested using triangulation techniques, both in terms of source and method, to ensure the validity and reliability of the findings. Data analysis referred to the interactive model of Miles and Huberman, which includes the stages of data reduction, data presentation, and iterative drawing of conclusions and verification until data saturation was reached. The results showed that residents of the East Sweta neighborhood have a positive perception of the use of the BRImo application. BRImo is considered to provide easy access, fast service, and a comprehensive range of features that support daily financial activities. From a security perspective, the public has considerable trust in BRImo's data protection system, which features PIN, OTP, and biometric authentication, although some still have concerns about technical glitches and potential cybercrime. In terms of benefits, BRImo is considered to help improve time efficiency, simplify financial management, and reduce dependence on conventional banking services. Furthermore, external factors such as social influence, promotion, and digital literacy also play a role in people's decision to use BRImo. Overall, this study concludes that BRImo is a key driver in driving the digitalization of the banking sector and expanding financial inclusion. The study also recommends that Bank Rakyat Indonesia (BRI) continue to improve system quality, expand service features, strengthen digital security, and develop strategies to increase digital literacy so that BRImo becomes more inclusive and able to reach all levels of society in the digital era. Keywords: public perception, BRImo, digital financial services, digital literacy, digital transformation